Features of Sperm Development: Spermatogenesis and Fertilization - Salokhiddinovna, Khalimova Yulduz (American Journal of Bioscience and Clinical Integrity, 2024)
Spermatozoa are highly specialized cells that are not capable of growth and division. The sperm consists of a head containing the paternal genetic material (DNA) and a tail that ensures its mobility. In the presence of a large nucleus, the sperm has practically no cytoplasm, the presence of which is characteristic of most cells of the body. The morphological heterogeneity of each man’s ejaculate is unique.